2019
DOI: 10.3390/ijms21010212
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Biomarkers in Liver Injury by Drugs, Herbs, and Alcohol: Tricky Dilemma after EMA Correctly and Officially Retracted Letter of Support

Abstract: Liver injuries caused by the use of exogenous compounds such as drugs, herbs, and alcohol are commonly well diagnosed using laboratory tests, toxin analyses, or eventually reactive intermediates generated during metabolic degradation of the respective chemical in the liver and subject to covalent binding by target proteins. Conditions are somewhat different for idiosyncratic drug induced liver injury (DILI), for which metabolic intermediates as diagnostic aids are rarely available. Although the diagnosis of id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 123 publications
(296 reference statements)
1
44
0
Order By: Relevance
“…Alcoholic-induced organ damage, as well as the MEOS, are subjects of continuous research and review of research [146,147]. It is mandatory that clinical, basic, and translational scientists collaborate on a common agenda for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic-induced organ damage, as well as the MEOS, are subjects of continuous research and review of research [146,147]. It is mandatory that clinical, basic, and translational scientists collaborate on a common agenda for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between alcohol and prescription drugs are common, particularly the additive effects with benzodiazepines and also with some of the antihistamine drugs; other interactions may occur with tricyclic antidepressants [137]. An important additional element of the hepatotoxic threat of alcohol is its enhancement of the hepatotoxic effects of other hepatotoxins (e.g., CCl 4 ) and even some drugs (e.g., acetaminophen) [138][139][140][141][142][143][144][145][146][147][148].…”
Section: Alcohol and Therapeutics Interactionmentioning
confidence: 99%
“…This certainly applies for evaluations and descriptions of any new diagnostic biomarker, as well. 65 Some diagnostic biomarkers are well established for HILI and DILI, but others came under scientific fire due to recent actions of the European Medicines Agency (known as the EMA) through the correct and official retraction of its earlier Letter of Support to promote biomarker research and use. 65 The retraction by EMA was the consequence of faulty results based on studies misconducted by not-further identified liver injury experts.…”
mentioning
confidence: 99%
“…65 Some diagnostic biomarkers are well established for HILI and DILI, but others came under scientific fire due to recent actions of the European Medicines Agency (known as the EMA) through the correct and official retraction of its earlier Letter of Support to promote biomarker research and use. 65 The retraction by EMA was the consequence of faulty results based on studies misconducted by not-further identified liver injury experts. 11,65 This official retraction represents currently, and in near future, a tricky dilemma for the scientific liver injury community.…”
mentioning
confidence: 99%
See 1 more Smart Citation